Neuroscience exploring the brain - Bear, Mark F.; Connors, Barry W.; Paradiso, Michael A. (Lippincott Williams & Wilkins, 2007)
Accompanying compact disc titled "Student CD-ROM to accompany Neuroscience : exploring the brain" includes animations, videos, exercises, glossary, and answers to review questions in Adobe Acrobat PDF and other file formats.
Keywords: Cerveau; Hersenen; Neurociencia; Neurofisiologia; Neurologie; Neurowetenschappen; Ruggenmerg; Brain; Neurosciences; Spinal Cord; Neurobiologie; Nervensystem; Neurowissenschaften; Hirnfunktion; Nervenzelle; Hirnforschung; Gehirn; Lehrbuch